Seven new species of New World Puliciphora Dahl (Diptera: Phoridae) with a new key to the Neotropical species - Henry, R.; Disney, L. (Zootaxa, 2003)
New species of Neotropical Puliciphora described are P. cacaulandiae, P. laranjae, P. longitergum, P. macrolunarum, P. mexicanae, P. reevesi, which is also recorded from the Nearctic Region, and P. parsetosa. Pachyneurella is returned to being a subgenus of Puliciphora. P. rata and P. tambopata are synonymised with P. venata. A new key to the females of the Neotropical species is provided.